Gestational age, birth weight, and blood culture microbial patterns in late-onset neonatal sepsis - Ramadhika, Muhammad; Iskandar, Stephen Diah; Yapiy, Ivana; Susanti, Yurika Elizabeth; Wijaya, Marcella Amadea; Rohsiswatmo, Rinawati (Paediatrica Indonesiana, 2024)
Background The three main causes of neonatal deaths in Indonesia according to the WHO are sepsis, prematurity, and asphyxia. A suboptimal hospital environment increases the risk of late-onset neonatal sepsis (LONS), which in turn can prolong hospital stays. Objective To assess for possible associations of bacterial patterns in neonates with LONS, prematurity, and/or low birth weight. Methods Medical record data of 1,706 hospitalized neonates who were treated for sepsis or other disease in the Neonatal Unit, Dr. Cipto Mangunkusumo Hospital (CMH), Jakarta in 2020 were analyzed retrospectively. A total of 262 neonates had proven LONS. We assessed for possible risk factors such as gestational age, birth weight, and cultured blood microbes. Results Out of a total of 1,706 neonates admitted to the neonatal unit, the incidence of proven LONS was 15.4%. LONS was more prevalent (58.4%) in preterm than in full-term (41.6%) neonates. The majority (67.6%) of subjects with proven LONS were neonates with low birth weight (LBW) (<2,500 grams), and the largest percentage of them (35.1%) was in the 1,500-2,500-gram group. Gram negative bacteria emerged as the predominant pathogens of LONS patients in our hospital; the most common were Klebsiella pneumonia, Acinetobacter spp., Escherichia coli, Enterobacter spp., and Pseudomonas aeruginosa. Conclusion The proportion of LONS among LBW and preterm neonates is significantly higher compared to normal birth weight and neonates. In our unit, LONS was mostly caused by Gram-negative bacteria. The antibiotic susceptibility of the various pathogens causing LONS in CMH should be tested and compared to the current empirical antibiotic guidelines used in CMH.